2009
DOI: 10.1074/jbc.m807000200
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of a Novel Gene, dapr, Involved in Skeletal Muscle Differentiation and Protein Kinase B Signaling

Abstract: The phosphatidylinositol 3-kinase (PI3K) signaling pathway has been associated with a variety of cellular functions ranging from cell cycle regulation to tissue development. Although years of research have extensively characterized this signaling pathway, little is known as to how specific cellular events are coordinated by its activation. Here we demonstrate that Dapr (differentiation-associated protein), a novel protein, appears to focus one aspect of this pathway by acting as a putative scaffold protein dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
(31 reference statements)
1
0
0
Order By: Relevance
“…The scaffold protein could operate selectively on activated c-Ras bound to the PI3K p110 subunit, but not bound to c-Raf. Similarly, it was reported that Dapr (differentiation-associated protein), a novel protein, acted as a scaffold protein for Akt during muscle differentiation [41]. These reports along with our data indicate that cells may have devised multiple mechanisms to activate PI3K with concurrent Raf inactivation downstream of c-Ras during myogenic differentiation.…”
Section: Discussionsupporting
confidence: 59%
“…The scaffold protein could operate selectively on activated c-Ras bound to the PI3K p110 subunit, but not bound to c-Raf. Similarly, it was reported that Dapr (differentiation-associated protein), a novel protein, acted as a scaffold protein for Akt during muscle differentiation [41]. These reports along with our data indicate that cells may have devised multiple mechanisms to activate PI3K with concurrent Raf inactivation downstream of c-Ras during myogenic differentiation.…”
Section: Discussionsupporting
confidence: 59%